The distraction potential of driving a partially automated vehicle through a construction zone - Francesco Biondi; Praneet Sahoo; Noor Jajo (Scientific Reports)
Abstract Partial driving automation is designed to control the vehicle’s speed and acceleration without input from the human driver on the condition that the driver maintains alertness. These systems are promised to make driving more convenient and safer, especially in increasingly demanding road conditions such as construction zones. Despite this, little knowledge is available on how these systems are used in these accident-prone areas and the effect they may have on drivers’ workload and glance allocation. This study aims to fill this gap by having participants drive a vehicle in partially automated and manual mode through three road sections: pre-construction, construction, and post-construction. Results show no differences in cognitive workload by driving mode or construction zone. An increase in glances directed away from the forward roadway toward the vehicle’s touchscreen was observed during partially-automated driving in the pre-construction zone, a pattern that, notably, continued on when driving throughout the construction zone. These findings adds to the literature on the human factors of partial automation. More importantly, because drivers failed to increase the amount of time looking at the forward roadway when entering the construction zone, they show the potential perniciousness of partially automated driving and the detrimental effect certain systems may have on safety risk.